2018
DOI: 10.3133/sir20185037
|View full text |Cite
|
Sign up to set email alerts
|

Hydraulic, water-quality, and temperature performance of three types of permeable pavement under high sediment loading conditions

Abstract: For an overview of USGS information products, including maps, imagery, and publications, visit https://store.usgs.gov. Any use of trade, firm, or product names is for descriptive purposes only and does not imply endorsement by the U.S. Government. Although this information product, for the most part, is in the public domain, it also may contain copyrighted materials as noted in the text. Permission to reproduce copyrighted items must be secured from the copyright owner.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 11 publications
1
16
0
1
Order By: Relevance
“…The infiltration rates for PA and PICB observed at the Taipei site were very similar to those reported by USGS [6] and the Montreal study [8], but quite different from results obtained by USEPA [1]. The inconsistency points to the fact that the actual field infiltration rate of porous pavement depends on many factors, such as installation and site environmental conditions, including underlying soil, runoff sediment load, etc.…”
Section: Infiltration Rate Monitoring Resultssupporting
confidence: 56%
See 1 more Smart Citation
“…The infiltration rates for PA and PICB observed at the Taipei site were very similar to those reported by USGS [6] and the Montreal study [8], but quite different from results obtained by USEPA [1]. The inconsistency points to the fact that the actual field infiltration rate of porous pavement depends on many factors, such as installation and site environmental conditions, including underlying soil, runoff sediment load, etc.…”
Section: Infiltration Rate Monitoring Resultssupporting
confidence: 56%
“…Additionally, about 5%-7% of the runoff infiltrated into the material later evaporates, which could help mitigate the urban heat-island effect [1], as stipulated by an earlier field test study in Arizona [5]. Another comprehensive study by the US Geological Survey [6] observed higher pollutant removal by PC but also a declining infiltration rate. Permeable pavements could reduce the "black ice" effect because water stored in the pores have temperatures (much water at different times, so many different temperatures) above freezing during winter weather.The transportation sector may potentially be a major user of permeable pavements.…”
mentioning
confidence: 99%
“…A second hypothetical option that was taken into consideration for flood risk management in case of the Glinščica river catchment is permeable concrete implementation. Permeable concrete is known to provide a cost-effective solution to the problem of localized urban flooding due to its ability of reducing storm-water runoff [39][40][41][42]. Moreover, permeable concrete (or pavement) also has multiple cold-weather benefits such as less road salt needs to be applied in winter with air stored in the material, which can have a positive effect on melting the snow or ice cover [43,44].…”
Section: Permeable Concretementioning
confidence: 99%
“…In sum, if generalizations are to be made in the presence of widespread terminological inconsistencies, U.S. governmental bodies tend to use: "porous asphalt" when referring to high void fraction continuous surface asphalt, either "pervious concrete" or "porous concrete" when referring to high void fraction continuous surface concrete, "permeable pavement systems" for grids of pervious or impervious pavers, and "permeable pavements" or "pervious pavements" as the over-arching term [38]. Again, exceptions are common, such as the U.S. Geological Survey's Scientific Investigations Report 2018-5037 using "permeable asphalt" and "permeable concrete" [41]. Researchers outside the U.S. are encouraged to consider the publications of their own government.…”
Section: Resolving Terminology Of Porous Permeable and Pervious Pavementsmentioning
confidence: 99%